Universal decolonization with octenidine: First experiences in a tertiary burn intensive care unit. Issue 1 (January 2019) - Baier, Claas; Ipaktchi, Ramin; Schwab, Frank; Smith, Andrea; Liu, Xiaofei; Ebadi, Ella; Limbourg, Anne; Mett, Tobias R.; Bange, Franz-Christoph; Vogt, Peter Maria
Abstract: Background: Burn patients are predisposed for nosocomial infections during their stay on a burn intensive care unit. Moreover, several outbreaks affecting burn units for example caused by Methicillin-resistant Staphylococcus aureus (MRSA) have been reported. One attempt to address these challenges is the use of universal decolonization. Methods: In 2015 we implemented universal decolonization for all burn patients using the antiseptic agent octenidine for intact skin and the nasopharyngeal mucosa. We conducted a retrospective analysis to evaluate the effect of the decolonization on primary, central line (central venous catheter)-associated bloodstream infections (CLABSI), the frequency of nosocomial clusters (4 or more cases with epidemiologic link and identical molecular pattern) with multidrug-resistant bacteria (MDRB) and the incidence of MRSA. Results: In the decolonization period a reduction of the incidence of CLABSI, nosocomial MRSA acquisition and the frequency of nosocomial MDRB clusters was observed. The incidence rate of CLABSI decreased from 2/1000 central venous catheter days in the pre-decolonization phase to 0.8/1000 central venous catheter days in the decolonization period, although this was not statistically significant. The implementation was accompanied by several feedback talks and training for the staff. The user experience was positive and no adverse effects occurred. Conclusion: Our results show that universal decolonization in burn patients using octenidine is a promising concept to address hospital acquisition of MRSA; occurrence of CLABSI as well as the spread of MDRB causing clusters. It is of high relevance to further assess the value of this measure in terms of reducing CLABSI in burn patients in larger study groups. Therefore further studies including more burn patients guaranteeing adequate sample size are needed.